2020
DOI: 10.3390/coatings10040382
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of an Aluminum/UV-Curable, Infrared, Low-Emissivity Coating Modified by Nano-Silica Slurry

Abstract: To improve the performances of UV-curable coatings, the effects of nano-silica slurry, aluminum and UV-curing time on the glossiness and infrared emissivity of UV-curable coatings were investigated by orthogonal experiments. The results showed that UV-curing time is a key factor affecting the performance of the coating. When the UV-curing time was increased from 30 to 360 s, the glossiness of the UV-curable coating slowly decreased from 11.1% to 9.0%. The L’ value decreased from 78.6 to 75.0. The infrared emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…(3),  n is the refraction angle corresponding to the incidence angle ,  a is the natural absorptance of the glass, mm -1 , s  is the total glass thickness, mm, n is the refractive index of the glass. All materials and technologies used in conventional smart windows [1][2][3][4][5][6][7][8] are also applicable to windows with grating filters.…”
Section: Methodsmentioning
confidence: 99%
“…(3),  n is the refraction angle corresponding to the incidence angle ,  a is the natural absorptance of the glass, mm -1 , s  is the total glass thickness, mm, n is the refractive index of the glass. All materials and technologies used in conventional smart windows [1][2][3][4][5][6][7][8] are also applicable to windows with grating filters.…”
Section: Methodsmentioning
confidence: 99%
“…other additives [14][15][16]. Among the potential metal powders, aluminum powder exhibits the best UV reflectivity: it can reflect more than 60% of the UV radiation in sunlight.…”
Section: Experimental 21 Materials and Sample Preparationmentioning
confidence: 99%
“…Metal powders can also be added to resins to take advantage of their excellent ultraviolet reflection characteristics. These metal powder additives can be used without any other additives [14][15][16]. Among the potential metal powders, aluminum powder exhibits the best UV reflectivity: it can reflect more than 60% of the UV radiation in sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials are the most popular modified materials in recent years [ 19 ] and have been applied to many modifiers, such as paints [ 20 , 21 ], wood, etc. It has been confirmed that nano-SiO 2 can improve the mechanical properties of wood [ 22 , 23 ] and dimensional stability [ 24 ], and some scholars have also used SiO 2 to improve the hydrophobicity and thermal insulation of wood [ 25 ].…”
Section: Introductionmentioning
confidence: 99%